Mice with humanized immune system as novel models to study HIV-associated pulmonary hypertension - Rodriguez-Irizarry, Valerie J.; Schneider, Alina C.; Ahle, Daniel; Smith, Justin M.; Suarez-Martinez, Edu B.; Salazar, Ethan A.; McDaniel Mims, Brianyell; Rasha, Fahmida; Moussa, Hanna; Moustaïd-Moussa, Naima; Pruitt, Kevin; Fonseca, Marcelo; et al. (Frontiers in Immunology, 2022)
People living with HIV and who receive antiretroviral therapy have a lifespan similar to uninfected people. However, persisting viral replication in the lungs sustains chronic inflammation, which may cause pulmonary vascular dysfunction and ultimate life-threatening Pulmonary Hypertension (PH). The mechanisms involved in the progression of HIV and PH remain unclear. The study of HIV-PH is limited due to the lack of tractable animal models that recapitulate infection and pathobiological aspects of PH. On one hand, mice with humanized immune systems (hu-mice) are highly relevant to HIV research but their suitability for HIV-PH research deserves investigation. On another hand, the Hypoxia-Sugen is a well-established model for experimental PH that combines hypoxia with the VEGF antagonist SU5416. To test the suitability of hu-mice, we combined HIV with either SU5416 or hypoxia. Using right heart catheterization, we found that combining HIV+SU5416 exacerbated PH. HIV infection increases human pro-inflammatory cytokines in the lungs, compared to uninfected mice. Histopathological examinations showed pulmonary vascular inflammation with arterial muscularization in HIV-PH. We also found an increase in endothelial-monocyte activating polypeptide II (EMAP II) when combining HIV+SU5416. Therefore, combinations of HIV with SU5416 or hypoxia recapitulate PH in hu-mice, creating well-suited models for infectious mechanistic pulmonary vascular research in small animals.